"I Learn as I Please": The Construction of Children's Knowledge in, and about, a Buenos Aires Neighbourhood. (25th February 2018) - Shabel, Paula
Abstract : This article summarises the findings of an ethnographic study among children of ages nine to fifteen who attend Aula Vereda, a community organisation in their neighbourhood with educational and recreational activities, once a week. On the assumption that children actively construct knowledge and do not merely repeat what adults impart, I'll identify three different ways in which these youths approach the instances of learning that the educators propose at the centre. These approaches, in turn, reveal a variety of cognitive productions and means for negotiating the spatial and generational meanings at work in the neighbourhood where they live.